Lectotypification of Moussonia (Gesneria) triflora (Gesneriaceae) - Angélica Ramírez-Roa (Revista Mexicana de Biodiversidad, 2022)
Moussonia triflora was originally published as Gesneria triflora in 1842 by M. Martens and H. Galeotti without the designation of a nomenclatural type. The analysis of the nomenclatural history includes its being part of 3 genera and as 2 species. The species is one of the 24 taxa included in Moussonia and is known only from the states of Oaxaca and Veracruz in Mexico. The lectotypification of the species is proposed. In addition, an amended description is provided, along with a listing of the examined specimens cited, as well as a key to distinguish similar taxa.